Non-accidental presence. The reception of Krzysztof Kieślowski in Russia - Viren, Denis (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2019)
Krzysztof Kieślowski is a cult figure among Russian moviegoers, but “proving” this is not as easy as in the case of the popularity of other Polish classic names in Russia, such as Andrzej Wajda and Krzysztof Zanussi. Placing Kieślowski on the list of Polish filmmakers who have influenced Russian culture in this or some other way is a not obvious move. The article is an attempt at exposing the reader to the presence of the director’s films in Russia through the history of the distribution of his films, an analysis of reviews by Russian authors and texts in which Kieślowski’s name appears. It also discusses references to his films in works by other filmmakers. It is complemented by the statements of two Russian directors who talk about the importance of Kieślowski in their work and academic practice.